2021
DOI: 10.1016/j.bjid.2021.101549
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine with azithromycin in patients hospitalized for mild and moderate COVID-19

Abstract: Objectives To assess the efficacy of hydroxychloroquine in combination with azithromycin in terms of clinical and biochemical outcomes in adult patients with COVID-19 hospitalized for acute respiratory distress syndrome (ARDS), and to describe the occurrence of adverse events. Method Retrospective comparative study, based in a quaternary private hospital in Rio de Janeiro, Brazil, involving 193 adult patients hospitalized for mild and moderate COVID-19 related ARSD, ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
9
0
2
Order By: Relevance
“…Forty-two articles were identified [ 7 , 9 , 12–51 ]. For 11 of them [ 12 , 15 , 17 , 19 , 21 , 23 , 25 , 31 , 32 , 34 , 47 ] it was possible to extract data necessary for comparing HCQ+AZM versus no HCQ+AZM. For all other studies, it was not possible to systematically distinguish if HCQ therapy was complemented or not with AZM.…”
Section: Methodsmentioning
confidence: 99%
“…Forty-two articles were identified [ 7 , 9 , 12–51 ]. For 11 of them [ 12 , 15 , 17 , 19 , 21 , 23 , 25 , 31 , 32 , 34 , 47 ] it was possible to extract data necessary for comparing HCQ+AZM versus no HCQ+AZM. For all other studies, it was not possible to systematically distinguish if HCQ therapy was complemented or not with AZM.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 74 articles reporting data on the safety of HCQ or CQ in patients treated for COVID-19 were found [ 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , ...…”
Section: Resultsmentioning
confidence: 99%
“…There were no significant differences between the pooled MD from imputed studies versus non-imputed studies (p = 0.17, see Supplementary Figure 9 ). Three observational studies [ 103 , 114 , 121 ] of the five remaining studies reported no significant differences between the median length of stay among patients taking hydroxychloroquine (with or without azithromycin) and patients receiving standard of care. The other two studies, specifically the RECOVERY trial [ 30 ] and a cohort study by Rosenberg et al [ 126 ], reported higher median lengths of stay in the hydroxychloroquine group compared with their respective control groups.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies [ 30 , 31 , 86 , 89 , 90 , 92 , 94 , 97 , 98 , 101 , 102 , 106 , 112 , 114 , 117–119 , 121 , 125 , 126 , 130 ] with 25,343 hospitalized COVID-19 patients assessed the effect of chloroquine and hydroxychloroquine on incidences of mechanical ventilation. The overall pooled OR was 1.26 (95% CI: 0.85–1.87) with significant and severe heterogeneity (I 2 = 87%; p Q <0.01).…”
Section: Resultsmentioning
confidence: 99%